PENGAWASAN PENYALURAN BAHAN BAKAR MINYAK OLEH DISPERINDAG KOTA PEKANBARU - Isnaini "; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Monitoring is known for an effort that systematic set of performance standards in planning to system design information feedback, to determine whether there has been a deviation, as well as to take the necessary corrective actions to ensure that all resources of the company or government has been used effectively and seefesien possible in order to achieve the objectives of the company or the government. This study aims to identify and analyze the implementation and monitoring of the Department of Industry and Trade of the City of Pekanbaru in order to address the distribution of subsidized fuel oil, considering the number of persons whose presence is not responsible peddle copies Subsidized Fuel Oil. Problems in this study is not optimal monitoring conducted by the city government agencies namely the Department of Industry and Trade as the vastness of space monitoring. In this study, the type of study is a qualitative research method conducted exploration / explorative which is one approach to research aimed at finding information about a topic / problem that is not fully understood by researchers or an interest and have not understood or have not been recognized y good. The research found first, the implementation of monitoring by the Department of Industry and Trade masi less than optimal. Second, retailers Subsidized Fuel Oil does not pay attention to safety aspects. Third, the lack of socialization masi filling stations in procedures and regulations have been established jointly with the government. fourth, masi lack of cooperation between the Department of Industry and Trade, the police, the gas stations, the public and others to minimize errors in the distribution of subsidized fuel oil for the right target in trade off this Subsidized Fuel Oil.Keywords: Monitoring, Distribution of Fuel Oil